EMPOWERMENT OF MSMEs BASED ON CASH WAQF IN THE ERA OF THE COVID-19 PANDEMIC - Siti Murtiyani Sukardi; Hery Sasono Yosoef (Kopertais Wilayah III Yogyakarta, 2022)
Indonesia is a country with a very large number of MSMEs spread throughout the country. During the Covid-19 Pandemic, there was an extraordinary shock so that many MSMEs went out of business and did not return to their activities. There are many factors that influence it, namely; limited capital, low level of education, lack of business knowledge, limited supporting technology owned by MSME actors in Indonesia. Empowerment of MSMEs based on cash waqf is one possible solution to help MSMEs rise and rebuild their businesses in the era of the Covid-19 Pandemic. The purpose of the study was to analyze the potential of cash waqf for the empowerment of MSMEs in Indonesia. Research based on empirical studies presented descriptively supported by valid data and information obtained from interviews and field observations. Techniques for collecting data from data sources from BAZNAS institutions, journals and articles from competent research results, which have been reviewed and analyzed as the basis for the theories used. The results of this study indicate that MSMEs really need a supply of cash funds to revive MSME businesses and it is necessary to develop MSME management so that they are stronger and can survive in the era of the Covid-19 Pandemic. Keywords: Empowerment, MSMEs, Cash Waqf, Covid-19 Pandemic